2016
DOI: 10.1016/j.biopsych.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressing Corticotropin-Releasing Factor in the Primate Amygdala Increases Anxious Temperament and Alters Its Neural Circuit

Abstract: Background Nonhuman primate models are critical for understanding mechanisms underlying human psychopathology. We established a non-human primate model of anxious temperament (AT) for studying the early-life risk to develop anxiety and depression. Studies have identified the central nucleus of the amygdala (Ce) as an essential component of AT’s neural substrates. Corticotropin-releasing hormone (CRH) is expressed in the Ce, has a role in stress, and is linked to psychopathology. Here, in young rhesus monkeys, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 94 publications
0
70
0
Order By: Relevance
“…Although the molecular underpinnings of dispositional negativity and its neural substrates remain poorly understood (Bastiaansen et al, 2014; Bogdan, Pagliaccio, Baranger, & Hariri, 2016; Christian et al, 2009), some promising candidates have recently been identified in humans (Buckholtz et al, 2008; Okbay et al, in press ), monkeys (Alisch et al, 2014; A. S. Fox et al, 2012; Kalin et al, in press ; Oler et al, 2009; Rogers et al, 2013; Roseboom et al, 2014), and rodents (Turner, Clinton, Thompson, Watson, & Akil, 2011). …”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%
See 1 more Smart Citation
“…Although the molecular underpinnings of dispositional negativity and its neural substrates remain poorly understood (Bastiaansen et al, 2014; Bogdan, Pagliaccio, Baranger, & Hariri, 2016; Christian et al, 2009), some promising candidates have recently been identified in humans (Buckholtz et al, 2008; Okbay et al, in press ), monkeys (Alisch et al, 2014; A. S. Fox et al, 2012; Kalin et al, in press ; Oler et al, 2009; Rogers et al, 2013; Roseboom et al, 2014), and rodents (Turner, Clinton, Thompson, Watson, & Akil, 2011). …”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%
“…Reduced BST activity has also been found in humans with OFC damage (Motzkin, Philippi, Oler, et al, 2015), suggesting that this circuit is conserved across primate species. Interestingly, viral vector manipulations that increase metabolic activity in the Ce—the other major component of the central extended amygdala—are associated with elevated metabolic activity in the OFC, increased functional connectivity between the Ce and OFC, and heightened signs of fear and anxiety during prolonged exposure to threat (Kalin et al, in press ). Conversely, Ce lesions are associated with reduced metabolic activity in the OFC (Machado et al, 2008).…”
Section: The Psychophysiology and Neurobiology Of Dispositional Negatmentioning
confidence: 99%
“…However, this tendency is itself the result of biological and environmental factors. The experience of frequent anxious states is assumed to feed back into biological factors through neuroplasticity (105) and epigenetic changes (106, 107), thereby opening a pathway for the effect of early stressful life events on biological vulnerability to the development of anxiety disorders (108110). Biological vulnerabilities are assumed to affect environment factors directly by increasing attention to environmental threats, as described in the section, “Trait Anxiety: Targets for Computational Studies” [for other ways in which trait vulnerabilities might promote aversive experiences, see Ref.…”
Section: State Anxiety Trait Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…The increase in anxious temperament correlated directly with increased fluorodeoxyglucose metabolism (by PET) and fMRI functional connectivity within a circuit that included the dorsal amygdala, orbital proisocortex/anterior insula and hippocampus (Kalin et al 2016). …”
Section: Recent Genetic and Molecular Findings In Humansmentioning
confidence: 99%